“Perfect Leader, Perfect Leadership?” Linking Leaders’ Perfectionism to Monitoring, Transformational, and Servant Leadership Behavior - Otto, Kathleen; Geibel, Hannah V.; Kleszewski, Emily (Frontiers in Psychology, 2021)
Despite the growing interest in perfectionism and its many facets, there is a lack of research on this phenomenon in the context of leadership. Attending to this lack, the present study is the first to investigate the relationship between the three facets of perfectionism, i.e. self-oriented, socially prescribed, and other-oriented perfectionism and three types of self-rated leadership behavior. In Study 1 (N = 184), leaders’ perfectionism and its association to their organizational goal-oriented leadership behavior, i.e. self-rated transactional (management by exception) and transformational leadership, was explored. In Study 2 (N = 186), the relationship of leaders’ perfectionism and their servant leadership as a people-centered leadership behavior was investigated. In line with the Perfectionism Social Disconnection Model (PSDM), we assumed other-oriented and socially prescribed perfectionism to be positively related to management by exception (i.e. monitoring behavior) and negatively to transformational and servant leadership whereas mainly the opposite pattern was predicted for self-oriented perfectionism. Our findings in Study 1 revealed a negative relationship between leaders’ self-oriented perfectionism as well as positive relationships of their other-oriented and socially prescribed perfectionism with management by exception while no substantial correlations with transformational leadership emerged. In Study 2 a negative association between other-oriented perfectionism and the forgiveness dimension of servant leadership was revealed, indicating a possible barrier to building interpersonal relationships of acceptance and trust. Additionally, self-oriented perfectionism turned out to be a rather favorable trait with regard to servant leadership.